What Apologia of Christianity Does Contemporary Europe Need? - Artemiuk, Przemysław (Ecumeny and law, 2024)
The purpose of this article is to answer the question: What kind of apologia of Christianity does modern Europe need? In the first part, the author, using the analytical method, refers to the works of three apologists (A. E. McGrath, G. Koukl, O. Guinnesse) and shows by their example how to practice apologia in the modern European context. The second, synthetic part is a presentation of the key features of apologia that should characterize the current defense of Christianity. The analyses carried out allow us to draw the following conclusions: first, modern apologists in their works show the topicality of apologetics, their analyses are primarily concerned with methodologicalissues. They pay attention not so much to the content that apologetic justification should contain, but are concerned with the form that modern apologetics should take; secondly, the apologists in question evidently link the issue of defending Christianity with evangelization. This is because they believe that apologetics plays an essential role during the preaching of the kerygma. The proclamation of the Gospel, its presentation, in order to be effective, must be combined with apologetics; finally, the most essential features of the modern defense, which remain necessary in the contemporary European context, are contextuality, supra-confessionalism, dialogicality, rationality,and cultural orientation.